2019
DOI: 10.1073/pnas.1902725116
|View full text |Cite
|
Sign up to set email alerts
|

The sRNA DicF integrates oxygen sensing to enhance enterohemorrhagicEscherichia colivirulence via distinctive RNA control mechanisms

Abstract: To establish infection, enteric pathogens integrate environmental cues to navigate the gastrointestinal tract (GIT) and precisely control expression of virulence determinants. During passage through the GIT, pathogens encounter relatively high levels of oxygen in the small intestine before transit to the oxygen-limited environment of the colon. However, how bacterial pathogens sense oxygen availability and coordinate expression of virulence traits is not resolved. Here, we demonstrate that enterohemorrhagicEsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 59 publications
0
48
2
Order By: Relevance
“…The authors of this study suggest that stability of DicF is differentially regulated such that it is more stable under anaerobic growth conditions and degraded faster under aerobic conditions. A very recent study found that four DicF orthologs encoded by different prophages in E. coli O157:H7 are produced under microaerobic growth conditions (31). These DicF sRNAs promote low oxygen-responsive virulence gene expression via base pairing-mediated regulation of a key virulence transcription factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of this study suggest that stability of DicF is differentially regulated such that it is more stable under anaerobic growth conditions and degraded faster under aerobic conditions. A very recent study found that four DicF orthologs encoded by different prophages in E. coli O157:H7 are produced under microaerobic growth conditions (31). These DicF sRNAs promote low oxygen-responsive virulence gene expression via base pairing-mediated regulation of a key virulence transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…DicA represses the dicBF operon promoter (which is similar to the λ phage P L promoter) and the natural condition(s) leading to induction of the operon are unknown (29). DicB and DicF are conserved in many strains of E. coli , and interestingly, many strains of pathogenic E. coli possess multiple cryptic prophages encoding dicBF operons (25, 30, 31).…”
Section: Introductionmentioning
confidence: 99%
“…When enterohemorrhagic Escherichia coli O157:H7 (EHEC), a food-borne pathogen, enters the digestive tract, it must adapt from oxygen rich environments to an increasingly oxygenlimiting environment toward the colon, where pathogens sense the differential gas concentrations and start to express their virulence factors (Melson and Kendall, 2019). As mentioned above, this is a key behavior of bacterial strains in order to set the basis of the infection onset, which seems to have evolved to start from a very low number of input cells (Van Elsas et al, 2011).…”
Section: Gastrointestinal Pathogenic Diseasesmentioning
confidence: 99%
“…As mentioned above, this is a key behavior of bacterial strains in order to set the basis of the infection onset, which seems to have evolved to start from a very low number of input cells (Van Elsas et al, 2011). DicF is a sRNA dependent on Hfq directly targeting the SD sequence of the transcriptional activator pchA, to promote its expression under low oxygen conditions (Melson and Kendall, 2019; Table 2). Ultimately, DicF has an effect over virulence by indirect increase of the expression of the locus of enterocyte effacement (LEE) pathogenicity island, but only when Hfq is present and oxygen concentration is very low (Figure 8).…”
Section: Gastrointestinal Pathogenic Diseasesmentioning
confidence: 99%
“…RNA purity was determined by measuring the A 260 /A 280 ratio and by performing PCR (35 cycles). qPCR was performed in a one-step reaction using an ABI 7500-FAST sequence detection system and software (Applied Biosystems) essentially as described previously (45). For each 10-l reaction mixture, 5 l of 2ϫ SYBR master mix (Ambion), 0.05 l of Multi-Scribe reverse transcriptase (Invitrogen), and 0.05 l of RNase inhibitor (Invitrogen) were added.…”
Section: Figmentioning
confidence: 99%